Identification of Antibacterial Activity of Hepcidin From Antarctic Notothenioid Fish - Liu, Mingli; Hu, Ruiqin; Li, Wenhao; Yang, Wenyi; Xu, Qianghua; Chen, Liangbiao (Frontiers in Microbiology, 2022)
Hepcidin is a small peptide composed of signal peptide, propeptide and the bioactive mature peptide from N terminal to C terminal. Mature hepcidin is an antibacterial peptide and iron regulator with eight highly conserved cysteines forming 4 intramolecular disulfide bonds, giving it a β sheet hairpin-like structure. Hepcidin homologs are found in a variety of vertebrates, especially fish, and their diversity may be associated with different habitats and different levels of pathogens. D.mawsoni, an Antarctic notothenioid fish that lives in the coldest water unlike most places of the word, with at least two hepcidin variants with 8 cysteines. We confirmed the formation process of activated mature hepcidins from D.mawsoni in CHO cell line, obtained recombinant hepcidin protein from prokaryotes, and characterized its binding ability and antibacterial activity against varying bacteria. The expression of hepcidin in CHO cell line showed that the prepropeptide of Dmhep_8cysV1 and Dmhep_8cysV2 cleavage into smaller mature peptide. The antibacterial assay and flow cytometry showed that Dmhep_8cysV1, Dmhep_8cysV2 and Drhep bound to different bacteria and killed them with different MIC (minimum inhibitory concentration). These data suggest that hepcidin plays an important role in the innate immunity of D.mawsoni and is of great value in improving resistence to pathogens.